Do Copy Number Changes in CACNA2D2, CACNA2D3, and CACNA1D Constitute a Predisposing Risk Factor for Alzheimer’s Disease? - Villela, Darine; Suemoto, Claudia K.; Pasqualucci, Carlos A.; Grinberg, Lea T.; Rosenberg, Carla (Frontiers in Genetics, 2016)
*Dysregulation of calcium (Ca2+) homeostasis is now being recognized to be a key step in the pathogenesis of Alzheimer’s disease (AD). Data from the literature, in particular the association between AD and polymorphism that interfere with Ca2+ homeostasis indicates the presence of genetic factors in this process; further, presenilins mutations, which are known to cause the familial form of AD, are involved in the regulation of intracellular Ca2+ stores. Here, we wish to draw attention to rare DNA copy number variations identified in two subjects with late-onset AD that led to partial or full duplication of genes that encode different subunits of the same type of voltage-gated Ca2+ channels; these duplications of voltage-gated Ca2+ channel genes is consistent with the critical role of calcium signaling in molecular processes underlying memory as has been demonstrated by several studies.